2013
DOI: 10.1161/circresaha.113.300512
|View full text |Cite
|
Sign up to set email alerts
|

Platelets as Cellular Effectors of Inflammation in Vascular Diseases

Abstract: Platelets are chief effector cells in hemostasis. In addition, they are multifaceted inflammatory cells with functions that span the continuum from innate immune responses to adaptive immunity. Activated platelets have key “thromboinflammatory” activities in a variety of vascular disorders and vasculopathies. Recently-identified inflammatory and immune activities provide insights into the biology of these versatile blood cells that are directly relevant to human vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
317
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(333 citation statements)
references
References 190 publications
(470 reference statements)
7
317
0
9
Order By: Relevance
“…Our findings, which focus on the endothelial sequelae of influenza infection, thereby are complementary and extend the notion that platelets contribute pathologically to influenza-induced acute lung injury. Given the importance of leukocytes and innate immunity in general to the host response to influenza infection (53) and the proposed role of platelets in regulating innate immunity (18,51), it is at least theoretically possible that platelet inhibition is harmful (54). Instead, we found that treatment with ASA improved survival, increased arterial oxygenation, and did not impair viral clearance in vivo.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our findings, which focus on the endothelial sequelae of influenza infection, thereby are complementary and extend the notion that platelets contribute pathologically to influenza-induced acute lung injury. Given the importance of leukocytes and innate immunity in general to the host response to influenza infection (53) and the proposed role of platelets in regulating innate immunity (18,51), it is at least theoretically possible that platelet inhibition is harmful (54). Instead, we found that treatment with ASA improved survival, increased arterial oxygenation, and did not impair viral clearance in vivo.…”
Section: Discussionmentioning
confidence: 60%
“…These circulating cytokines likely stimulate platelets (50) and endothelial cells, promoting platelet-endothelial adhesion. Regardless of the specific stimulus, adherent platelets become activated and regulate numerous facets of the inflammatory response, including the release of further proinflammatory mediators and the formation of neutrophil extracellular traps (18,51) that together contribute to tissue injury. Thus, the relative contribution of endothelial infection to this sequence of events is unknown and technically difficult to assess, as preventing the infection of any one tissue alone in vivo is not currently feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet activating factor (PAF) identified as 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine (Demopoulos, Pinckard, & Hanahan, 1979) has been recognized as one of the most potent lipid inflammatory and thrombotic mediator that activates various cells through its specific receptor, such as platelets (Demopoulos et al, 2003). Activated platelets are important contributors to thrombosis and inflammation, and represent an important linkage between inflammation, thrombosis, and atherogenesis (Demopoulos et al, 2003;Fuentes et al, 2013;Gawaz, Langer, & May, 2005;Rondina, Weyrich, & Zimmerman, 2013). In vitro inhibition of PAF induced platelet activation from food components has been used as a research tool to investigate the nutritional value of those foods and their possible preventive effect against chronic disease development when consumed as part of a balanced diet (Karantonis, Antonopoulou, & Demopoulos, 2002Karantonis et al, 2008;Nomikos, Karantonis, Skarvelis, Demopoulos, & Zabetakis, 2006;Nomikos et al, 2007).…”
Section: In Vitro Anti-thrombotic/antiinflammatory Activitymentioning
confidence: 99%
“…Their activation can alter the properties of leukocytes, endothelial cells and other vascular cells (Smyth et al,200). They play an important part in cellular effectors of inflammation in vascular diseases (Rondina et al, 2013). They are first responders in vascular injury and endothelial disruption.…”
Section: Discussionmentioning
confidence: 99%